A study on the factors that influence students’ performance using TPACK model / Hassan Wira - Hassan Wira (Faculty of Business Management, 2017)
I am conducting a research study titled A Study on Factors That Influence Students’ Performance Using TPACK Model at UiTM Melaka City Campus. Technology nowadays is really important in our daily life, including in learning process. The purpose of this research is to investigate the relationship between Technology, Pedagogy And Content Knowledge (TPACK) and Students’ Performance. There are three independent variables and one dependent variable in this study which are Technology Knowledge, Pedagogy Knowledge and Content Knowledge as independent variables, IV while Students’ Performance as dependent variable, DV. I would study the relationship between each independent variables and dependent variable that is based on the result from the questionnaire that I would distribute to students of part 5 of UiTM Melaka City Campus by using SPSS software.